SISTEMA PENITENCIARIO ECUATORIANO: UN DEBATE DESDE LA PERSPECTIVA DE SU REALIDAD CRIMINOLÓGICA TRAS LA BÚSQUEDA DE UN MEJOR FUTURO - González Chamba, Servio Patricio (2015)
This paper contains a development on the Ecuadorian prison system really, really related to the aspect of social reintegration, which is the basis of the penal system, since its orientation is not to punish the offender, but to help disrobe that led to crime and provide assistance so that it becomes a human being useful to society. Scientific Problem is defined as: In the Ecuadorian prison reality there are limitations to the effective implementation of re-socializing treatment of those sentenced to deprivation of liberty, which hinders the achievement of the purposes of punishment, specifically the detention. As the General Objective: To determine, from a criminological perspective, the main difficulties in the normative and practical presents the Ecuadorian prison system, with the aim of providing solutions to them, from the legal point of view. And specific objectives: 1. Analyze the historical nature of the prison as an institution, state of crisis and the prospect of resolving the prison problem. 2. Exposing the theoretical arguments that helps build a prison legislation which aims to seek the effective enforcement of custodial sentences. 3. Rate, from the point of practical difficulties that arise in prison reality of Ecuador, which hinder the proper treatment of prisoners and the end of rehabilitation of the convicted. The working hypothesis is aimed at the following address: You can do a better job of correctional treatment in Ecuador, if it determines the set problems that occur in it, in order to implement such treatment an effective policy implementation of sanctions in the search for true social rehabilitation of sentenced to imprisonment. This is a fundamentally theoretical study, where we use as research methods: 1. Historical Logic: This method has allowed us to explain and understand why the prison is an institution in crisis and the importance of solutions to the institution. 2. Legal theorist: It is that from general theoretical principles and concepts of the Theory and Philosophy of Law and by logical procedures, we aim to achieve deductively establish the foundation and essence of the phenomenon of the prison crisis. Implementation and the results provided become important for our theoretical research, since it has allowed the development of concepts and the theoretical research. 3. Content Analysis. The literature review was the technique mainly used to obtain information. For the development of this research is still as scientific methodology, the following tasks:  Definition of the research object and the focus of the same;  Review of the literature and exploratory work item;  Development of the methodological design. Field work: applying the techniques of group dynamics and in-depth interviews and data analysis. Writing the final report. With the completion of this research, we propose the following results: 1. Substrate form a theoretical base your demonstration of the prison crisis, for the implementation of a strategy toward improving legal philosopher of the institution under review. 2. Provide theoretical foundations for the development of a prison law whose center is to improve the behavior of the punished. 3. Offer of evidence of the crisis facing the prison system in Ecuador, and provide solutions towards improvement. At the end of the investigation, and as a result of its implementation, we pronounce our conclusions and recommendations relevant to understand.